Beyond us prototyping design and future building solutions through a multi-disciplinary design school and innovation hub - Salerno, Alessandro (My University, 2018)
The nineteenth and early twentieth century were characterised by the establishment, diversification, and specialization of fields of thought. Many disciplines came into being, developing independently of one another and in some cases dividing into clearly compartmentalized sub-disciplines. Although this division has been the basis of education for centuries, there is a growing realisation that for education to be effective, it must help the learners to seek answers to some of the fundamental real-life problems around them. This cannot be achieved through the current hierarchical and discipline-oriented approach, as life and its current problems are not divided up into disciplines. The argument for multiple disciplinarity is not that the disciplines represent a false theory of knowledge but rather that they are not a complete statement if we take them on their own. It is in the interconnections, the integration, that they attain their most effective use. Therefore, this project aims to provide a suitable architectural space in which a multiple disciplinary approach to education can be promoted. The project itself utilised a multiple disciplinary approach in the design process which was influenced by the history and existing structures of the site, neo-futurist designs and principles, the chemical and physical properties of gas, and particle architecture. The proposed building provides all of the required program elements while promoting collaboration and multiple disciplinary learning.